Precision 96-Channel Dispenser for Microchemical Techniques. (February 1996) - Stanchfield, J.; Wright, D.; Hsu, S.; Lamsa, M.; Robbins, A.
A new automated 96-channel microdispenser is described for precise, high-speed dispensing of microliter volumes of reagents. The Hydra-96™ is a programmable instrument composed of 96 glass syringes arrayed in a microplate format that fills and dispenses in unison under computer control. Studies show the instrument has less than a 2% coefficient of variation (CV) across the syringe array when dispensing between 0.5 and 20.0 μL of reagent. Blot hybridization studies demonstrate a simple rinsing protocol using 2% bleach that efficiently cleans the system of DNA without affecting subsequent PCRs. Current uses of the instrument in assembling microassays used in large-scale genetic mapping and sequencing projects and compound library screening are discussed.